The role of concurrent chemotherapy for stage II nasopharyngeal carcinoma in the intensity-modulated radiotherapy era: A systematic review and meta-analysis. - Fang Liu; Tao Jin; Lei Liu; Zhongzheng Xiang; Ruonan Yan; Hui Yang (PLoS ONE)
Objectives To compare clinical outcomes of concurrent chemoradiotherapy (CCRT) with those of radiotherapy alone for stage II nasopharyngeal carcinoma in the intensity-modulated radiotherapy (IMRT) era. Materials and methods We comprehensively searched PubMed, Embase, and the Cochrane Library to identify eligible studies. Overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS), locoregional recurrence-free survival (LRRFS) with hazard ratios (HRs), and toxicities with odd ratios (ORs) were analyzed. Results A total of seven studies met the criteria, with 1302 patients who were treated with IMRT alone or IMRT plus concurrent chemotherapy. No significant survival benefit was shown by CCRT regardless of OS (HR = 1.17, 95% CI 0.73-1.89, P = 0.508), PFS (HR = 0.76, 95% CI 0.38-1.50, P = 0.430), DMFS (HR = 0.89, 95% CI 0.33-2.41, P = 0.816), or LRRFS (HR = 1.03, 95% CI 0.95-1.12, P = 0.498). Additionally, CCRT notably increased the risk of acute grade 3-4 leukopenia (OR = 4.432, 95% CI 2.195-8.952, P < 0.001), compared to IMRT alone. Conclusion Adding concurrent chemotherapy to IMRT led to no survival benefit and increased acute toxicity reactions for stage II nasopharyngeal carcinoma.